2017
DOI: 10.1002/jcla.22153
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor‐α ‐308 G/A gene polymorphism with coronary artery diseases: An evidence‐based study

Abstract: Background Coronary artery disease (CAD) is the leading cause of death worldwide and remains a major health problem, providing the rationale for identification of molecular markers for detection of individuals at high risk of developing CAD. Tumor necrosis factor‐α (TNF‐α) plays a crucial role in the pathogenesis of CAD. We have therefore explored the association of TNF‐α 308 (G/A) gene polymorphism in 903 individuals with/without CAD. Methods TNF‐α 308 gene polymorphism was analyzed in 903 subjects of whom 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Control group consisted of 136 people, among them -63 men and 73 women aged from 45 up to 65 years without cardiovascular pathology and serious chronic illness [1]. 266 patients with CHF and EF lower than 40 % have been included in other research, no associations between TNF-α plasma concentration and TNF-α (308 A/G, 238 A/G, TNF beta Ncol and 3TACE) gene polymorphism have been observed [2].…”
Section: Introductionsupporting
confidence: 45%
“…Control group consisted of 136 people, among them -63 men and 73 women aged from 45 up to 65 years without cardiovascular pathology and serious chronic illness [1]. 266 patients with CHF and EF lower than 40 % have been included in other research, no associations between TNF-α plasma concentration and TNF-α (308 A/G, 238 A/G, TNF beta Ncol and 3TACE) gene polymorphism have been observed [2].…”
Section: Introductionsupporting
confidence: 45%
“…One explanation for the higher -308A allele frequency in the no-OSA group in our study might be the confounding effect of other comorbidities such as obesity, hypertension and diabetes mellitus and/or CAD per se, given that those individuals without OSA were not healthy controls. Similar to OSA, CAD is an inflammatory condition mediated by the activity of pro-inflammatory cytokines including TNF-α [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of TNF-α gene polymorphism in CAD pathogenesis has been extensively investigated with inconsistent results. Some researchers have reported that TNF-α -308G/A polymorphism is implicated in CAD development [ 37 , 38 ], whereas some others reported no evidence in this context [ 39 ]. It is suggested that the implication of the polymorphism in CAD pathogenesis differs between geographical ethnicities, and there was no significant association of TNF-α -308G/A polymorphism with the development of CAD according to a recent meta-analysis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken as a whole, our pilot gene associations were in the expected direction; that is, we observed increased risk of symptoms in the presence of TNF risk alleles. A number of studies found that, among cytokine SNPs, TNF rs1800629 and IL6 rs1800795 were significantly associated with CAD, and these SNPs were important risk factors for the development of ACS (Ansari et al, 2017;Babu et al, 2012;Kazemi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%